INNOWACJA NA DRODZE PRAKTYCZNIE UŻYTECZNEJ APLIKACJI? PRZYCZYNEK NA RZECZ DIALOGU POMIĘDZY GLOTTODYDAKTYKĄ A JĘZYKOZNAWSTWEM - Pieklarz-Thien, Magdalena (Neofilolog, 2018)
Innovation in addition to rationalization, optimization and professionalization contributes to the cognitive interest of many scientific disciplines, where research is carried out for the use of specific areas of practical activities. Of particular interest in the context of glottodidactics is both its theoretical (scientific research) and practical (implementation) dimension, implying the proposal of practical applications in specific educational contexts. This article is a trial undertaking to consider the problem of innovation using the incorporation and adaptation of the latest findings and results of language research in glottodidactics as an example. Considerations are made using examples from German linguistics and German as a foreign language didactics and constitute a contribution to the discussion of the identity and autonomy of glottodidactics as a science.